The Relationship of Student Learning Motivation Against Student Learning Independence on Dynamic Electric Material - Dina fajrin; Dwi fajar saputri; Ira Nofita Sari (Universitas Lambung Mangkurat, 2020)
This study analyses the relationship between student' learning motivation and student learning independence on dynamic electrical material in class IX SMP Negeri 7 Sungai Raya. The research method used is descriptive, with a correlative form of research. The population is 117 student from all grade IX students of SMP Negeri 7 Sungai Raya, the sample used in this study was 89 students. The sampling technique uses simple random sampling. Values used for independent and bound variables use a questionnaire. The Values analysis technique used is descriptive statistics and correlations with the coefficient of determination at a significant level of 5%. The result of research found that (1) student motivation in class IX SMP Negeri 7 Sungai Raya in the good category; (2) the independence of student learning was in a good category; and (3) there was a positive and significant relationship between student motivation on student learning independence. So it can be concluded that the greater the student's learning motivation, the greater their learning independence.